1996
DOI: 10.1128/mcb.16.8.4414
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Strand Break within a Yeast Artificial Chromosome (YAC) Containing Human DNA Can Result in YAC Loss, Deletion, or Cell Lethality

Abstract: Human chromosomal DNA contains many repeats which might provide opportunities for DNA repair. We have examined the consequences of a single double-strand break (DSB) within a 360-kb dispensable yeast artificial chromosome (YAC) containing human DNA (YAC12). An Alu-URA3-YZ sequence was targeted to several Alu sites within the YAC in strains of the yeast Saccharomyces cerevisiae; the strains contained a galactose-inducible HO endonuclease that cut the YAC at the YZ site. The presence of a DSB in most YACs led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 38 publications
(47 reference statements)
4
35
0
Order By: Relevance
“…By introducing NHEJ, cells of higher eukaryotes rapidly restore integrity in their large genome, relying on HRR only to restore critical DNA sequences at a later time. This controlled approach to HRR may reduce illegitimate recombination events that could be initiated by repeat sequences (Bennett et al, 1996) and may explain the suppression observed in the utilization of HRR for the initial rejoining event (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing NHEJ, cells of higher eukaryotes rapidly restore integrity in their large genome, relying on HRR only to restore critical DNA sequences at a later time. This controlled approach to HRR may reduce illegitimate recombination events that could be initiated by repeat sequences (Bennett et al, 1996) and may explain the suppression observed in the utilization of HRR for the initial rejoining event (see below).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that down-regulation of HRR in vertebrate cells aims at reducing the occurrence of illegitimate recombination events supported by repeated sequences in the presence of DSBs (Bennett et al, 1996(Bennett et al, , 1997. To counteract associated defects on DNA DSB repair, DNA-PKcs, an enzyme not present in yeast, may have evolved in vertebrate cells to accelerate NHEJ.…”
Section: Hard-wiring' In the Utilization Of Hrr And Nhej In Eukaryotimentioning
confidence: 99%
“…Thus, even in the presence of various mechanisms preventing DSB formation from closely spaced DNA damages on opposing DNA strands, there is still a risk of DSB-induced cytotoxicity, as only a small number of DSBs is sufficient to kill a cell (36). Such DNA damages can be found within DNA damage clusters induced by ionizing radiations (2).…”
Section: Fen-1 and Double-strand Dna Breaksmentioning
confidence: 99%
“…As illustrated in Figure 1, we assume that the burst size decreases when a double-strand break of one of the coinfecting phages remains unrepaired. This assumption is based on the experimental evidence that a single unrepaired double-strand break on a plasmid molecule or a yeast artificial chromosome induces lethality to a cell (Bennett et al 1993(Bennett et al , 1996. We thus introduce another parameter of burst size under induction of damage to the host cell physiology b 1 , which is less than or equal to default burst size b 0 .…”
Section: Modelsmentioning
confidence: 99%